Customised production of injection moulded parts from recycled materials using rapid tooling approach and coupled injection moulding-thermal and mechanical simulation - Szabolcs Krizsma; András Suplicz; Dániel Gere (Results in Engineering)
Additive manufacturing is the state of the art in modern tool making. It makes the low-volume production of polymeric parts and prototype moulds feasible. Injection moulded parts can be customised flexibly and fast with prototype polymeric moulds. Another trend in the plastics industry is the widespread use of recycled materials to reduce environmental impact. In this article, we introduce a novel technological concept: applying prototype injection moulds to process recycled materials. We investigated three materials: original PP, a recycled PP-HDPE mixture, which is a commercially available injection moulding material and a recycled PA6 that is difficult to mould due to the high melt temperature. All three materials were injection moulded successfully with outstanding product quality. The injection moulding process was modelled with a coupled injection moulding simulation—finite element thermal and mechanical simulation. The presented novel modelling method proved accurate. The injection pressure, temperature and strain results of the simulations showed excellent agreements with the measured results. The application of additively manufactured prototype moulds to produce parts from recycled materials is definitely a novelty.